KONSEP BERPUASA YANG BENAR MENURUT YESAYA 58:6-7 DAN IMPLIKASINYA BAGI GEREJA MASA KINI - Suparna (Jurnal Teologi Biblika, 2023)
Fasting is something that is important to Christians from time to time until now. There are still Christians who do not understand the correct concept and purpose of fasting which is a separate problem which of course has an impact on the practice of fasting which is wrong and displeases God. The purpose of this study is to provide an explanation of the correct concept of fasting according to Isaiah 58:6-7 and its implications for the church today. This study uses qualitative research methods with literature studies and inductive interpretation of the meaning of the text. The result of the research is that fasting must be done with the right concept. Outwardly the Israelites fasted and continued to worship God, but with a wrong understanding of the concept so that this did not please God's heart, but instead made God angry because of their hypocrisy. Outwardly the Israelites fasted, but in fact crime remained a part of their daily lives, by living only caring about themselves and not caring about others. It is this correct concept of fasting that must be understood and exists in today's church. Keywords: Concept, Fasting, True, Hypocrite.